Environmental and hydroclimatic factors influencing Vibrio populations in the estuarine zone of the Bengal delta - Neogi, Sucharit Basu (2018)
The objective of this study was to determine environmental parameters driving Vibrio populations in the estuarine zone of the Bengal delta. Spatio-temporal data were collected at river estuary, mangrove, beach, pond, and canal sites. Effects of salinity, tidal amplitude, and a cyclone and tsunami were included in the study. Vibrio population shifts were found to be correlated with tide-driven salinity and suspended particulate matter (SPM). Increased abundance of Vibrio spp. in surface water was observed after a cyclone, attributed to re-suspension of benthic particulate organic carbon (POC), and increased availability of chitin and dissolved organic carbon (DOC). Approximately a two log10 increase in the (p < 0.05) number of Vibrio spp. was observed in < 20 μm particulates, compared with microphytoplankton (20–60 μm) and zooplankton > 60 μm fractions. Benthic and suspended sediment comprised a major reservoir of Vibrio spp. Results of microcosm experiments showed enhanced growth of vibrios was related to concentration of organic matter in SPM. It is concluded that SPM, POC, chitin, and salinity significantly influence abundance and distribution of vibrios in the Bengal delta estuarine zone.